The expression 3n + 4 represents a mathematical operation where 3 is multiplied by the variable n and then 4 is added to the result. The expression cannot be simplified further without knowing the specific value of n. If n is a specific number, you can substitute that number in place of n to find the exact value of the expression.
3n x 3n = 9n if 9n = 36 then n = 36/9 = 4
2+3n+2+9n would equal 4+12n after adding all like numbers.
When n = 4, 3n = 3*4 = 12
3n+2+3n+2=6n+4
Gather like terms. The - 2 and 4; the 7n and 3n. 7n - 2 + 3n + 4 = 10n + 2
3n x 3n = 9n if 9n = 36 then n = 36/9 = 4
3n2-8n+4 = (3n-2)(n-2) when factored
2+3n+2+9n would equal 4+12n after adding all like numbers.
3n and n = 4? 3n ( the four replaces the n 3(4) = 12 =======
3n + 2 + (3n + 3 - 3n + 1) = 3n + 2 + (3n + 3 - 3n + 1) = 3n + 2 + (4) = 3n + 6
When n = 4, 3n = 3*4 = 12
They are two terms of an algebraic expression in the form of 45-3n
3n^4 divided by 3n^3 = n
3n+2+3n+2=6n+4
4n = 3n + 44n - 3n = 3n - 3n + 4n = 4check:4n = 3n + 44(4) =? 3(4) + 416 =? 12 + 416 = 16 True
Gather like terms. The - 2 and 4; the 7n and 3n. 7n - 2 + 3n + 4 = 10n + 2
3n + 4 = 7(- 4 from both sides)3n = 3(divide both sides by 3)n = 1